Impact of Women Driving Rights on Adoption and Usage of E-hailing Applications in Saudi Arabia - Muhammad Ahsan Qureshi; Azra Shamim (Acta Informatica Pragensia, 2023)
E-hailing applications are becoming popular around the globe. However, the motivations and barriers to use these applications may differ in different countries. Therefore, the aim of current work is to explore noteworthy factors affecting the acceptance of the e-hailing application 'Careem' in the context of Saudi Arabia. Due to recent driving permission given to women in Saudi Arabia and the lesser acceptance of public transport in Saudi Arabia, this study is of fundamental importance. To achieve the purpose of this study, the technology acceptance model is extended by adding external variables: perceived convenience, perceived accessibility and confirmation. Careem application users participated in a survey that was created and circulated to acquire measurement of the factors. The data gathered from 428 users are analysed using structural equation modelling. The findings show that perceived usability, perceived ease of use, perceived usefulness and perceived convenience are crucial and direct predictors of intention to use e-hailing applications, while confirmation and perceived accessibility are discovered to be factors that have an impact on the intention to use e-hailing applications. The findings of the study highlight the significant contributing factors in the adoption and usage of e-hailing applications. Also, these factors can assist designers and developers of these applications to develop applications having high acceptance and usage.